(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: One of the most significant determinants of risk perceptions and coping mechanisms is gender, which reflects the public’s propensity to embrace health initiatives and exercise caution. This study aims to understand the gender differences in perspective regarding government policies in combating COVID-19 pandemic. Subjects and methods: This analytical cross-sectional study was conducted as an online google survey from April to September 2021 in Lahore using a non-probability convenience sampling technique. SPSS version 23 was used for the analysis of the data, which was gathered using a self-structured questionnaire from 200 participants. Chi-square test was applied to deal with qualitative variables and a p-value <0.05 was considered significant. Results: Out of 200 respondents, 92(46%) were males and 108(54%) were females. Mean age of the participants was 25.8+ 6.6years. Significant differences were found in perceptions between males & females in containing Corona virus by putting restrictions on wedding halls and social gatherings (p-value=0.05) as well as government’s decision of closing the educational institutions and online learning classes (p-value=0.035). Significant differences were also seen in perceptions of both genders regarding strict punishment for those who break SOP’s in form of fines (p-value=0.001), vaccination mandatory for every individual (p-value=0.008) and PCR diagnostic test should be done free of cost (p-value=0.003). Conclusion: Women are more inclined to agree with and follow restraining measures and laws, and to view the pandemic as a very serious health issue. This data reveals a realm of gender disparities as well as behavioral changes in reaction to a new risk, which has significant implications for gender-based public health policy and COVID-19 communication.